Ophryocystis sitonae sp. nov., (Neogregarinida: Ophryocystidae) parasitizing Sitona humeralis Stephens, 1831 (Coleoptera: Curculionidae). (January 2022) - Yıldırım, Hilal; Tosun, Onur; Bekircan, Çağrı
Abstract: Sitona humeralis Stephens 1831 (Coleoptera: Curculionidae) is an important pest of the Medicago and Vicia species in Turkey, and this study was conducted the determine the natural pathogens of this beetle. In the present study, a new neogregarine was observed in Malpighian tubules of the S. humeralis, collected from Ordu (Turkey) on the wild Medicago species. The yellowish oocysts were the most notable feature of the current neogregarine. The Giemsa-stained mature oocysts were fusiform shaped and measured 8.7 ± 0.7 (7.12–11.11) μm in length and 4.1 ± 0.3 (3.05–5.01) μm in width. The smooth oocyst wall was relatively thin (175–230 nm), and polar plugs were non-evident (weight = 380 nm, height = 500 nm). The 18S rDNA gene of the current neogregarine was sequenced and compared with fifteen sequences from GenBank. Morphological, ultrastructural, and molecular features indicate that the described neogregarine in S. humeralis differed from the all known Ophryocystis species and named here Ophryocystis sitonae sp. nov. Highlights: First record of neogreganial infection from Sitona humeralis (Coleoptera: Curculionidae). Infection is only observed in the Malpighian tubules of the host. Oocysts have a yellowish color. Oocyst was measured 8.7 ± 0.7 (7.12–11.11) μm in length and 4.1 ± 0.3 (3.05–5.01) μm in width.